2004
DOI: 10.1007/s00106-003-0953-4
|View full text |Cite
|
Sign up to set email alerts
|

Tuberkul�se Spondylitis mit retropharyngealer Abszedierung

Abstract: In the industrialized countries, the last 15 years have seen an increasing rate of cases of tuberculosis. However, upper cervical spine tuberculosis involving a cold retropharyngeal abscess is extremely rare. We report on a 58 year old female from Sri Lanka presenting with unspecific neck pain and stiffness. She was diagnosed as having extensive tubercular osteodestruction of the second cervical spine body, including epidural and large retropharyngeal abscesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…According to Lübben et al [14], cervical spine tuberculosis with a cold retropharyngeal abscess is extremely rare, and it should be suspected in a person who presents with a destructive lesion of the vertebra and a retropharyngeal mass. In our study, the diagnosis of tuberculous retropharyngeal abscess was made before clinical and radiological arguments (image of spondylodiscitis) as well as the positivity of tuberculin test.…”
Section: Discussionmentioning
confidence: 99%
“…According to Lübben et al [14], cervical spine tuberculosis with a cold retropharyngeal abscess is extremely rare, and it should be suspected in a person who presents with a destructive lesion of the vertebra and a retropharyngeal mass. In our study, the diagnosis of tuberculous retropharyngeal abscess was made before clinical and radiological arguments (image of spondylodiscitis) as well as the positivity of tuberculin test.…”
Section: Discussionmentioning
confidence: 99%
“…Radionuclide scanning findings are not specific for Pott disease. Gallium and technetium bone scans yield high falsenegative [8][9][10][11][12].…”
Section: Scintigraphymentioning
confidence: 99%
“…The signs of infection may be lacking in certain situations of immune suppression such as diabetes, acquired immune deficiency syndrome (AIDS), malignancy, chronic alcoholism and tuberculosis. 10,11 Treatment wise, the decision of medical or surgical intervention depends on the general condition of the child, size of the abscess, potential complications and surgical accessibility. 9 A number of authors have suggested using surgery only when patients do not respond to medical treatment.…”
Section: Case Reportmentioning
confidence: 99%